PENGARUH GAYA KEPEMIMPINAN, BUDAYA KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Rike Selviasari (Istithmar: Jurnal Studi Ekonomi Syariah, 2020)
This study aims to determine, (1) whether leadership style, work culture and work discipline in a simultaneous persial significantly influence employee performance at PT. Bank Rakyat Indonesia (Persero), Tbk. Nganjuk Branch. (2) Does the work culture significantly influence employee performance at PT. Bank Rakyat Indonesia (Persero), Tbk. Nganjuk Branch (3) Does work discipline have a significant effect on employee performance at PT. Bank Rakyat Indonesia (Persero), Tbk. Nganjuk Branch. This research includes the type of quantitative research. The population in this study are all employees in the company at PT. Bank Rakyat Indonesia (Persero), Tbk. Nganjuk Branch which numbered 112 employees. The instruments used in this study were questionnaires used to reveal data on leadership research variables, work culture and work discipline. Data analysis techniques used were Validity Test, Reliability Test and Classic Assumption Test. The results of this study are, (1) The leadership style in a significantly significant way affects the performance of employees at PT. Bank Rakyat Indonesia (Persero), Tbk. Nganjuk Branch (2) The work culture in a significant way has an effect on the performance of employees at PT. Bank Rakyat Indonesia (Persero), Tbk. Branch Nganjuk (3) Work discipline in a significant manner influences employee performance at PT. Bank Rakyat Indonesia (Persero), Tbk. Nganjuk Branch.